(untitled) (Bangladesh Journal of Microbiology, 2024)
The Dengue virus is a prevalent mosquito-borne disease, and its global incidence has been steadily increasing due to the favorable environmental conditions that promote mosquito breeding, primarily influenced by rising temperatures. Bangladesh has been particularly hard-hit by an intense and ongoing outbreak, resulting in a surge of cases and fatalities. Effective management of this disease necessitates the implementation of robust public health measures, including rigorous surveillance and early diagnosis. While serological tests are commonly employed in clinical diagnosis, molecular methods hold a critical role in identifying the specific Dengue virus strain, thereby contributing to a more comprehensive understanding of disease severity. This article serves as an extensive review, delving into various molecular testing techniques employed for both surveillance and clinical diagnosis. It offers valuable insights for research and clinical laboratories engaged in the detection of Dengue virus RNA in mosquitoes, environmental samples, and clinical specimens. The methods covered encompass a spectrum of approaches, including conventional PCR, isothermal amplification, real-time RT-PCR, Sanger sequencing, and whole-genome sequencing, providing a holistic overview of the available techniques. These methods play pivotal roles in clinical diagnosis, outbreak analysis, vector surveillance, and vaccine development. Furthermore, the article underscores the importance of integrating these techniques into existing healthcare systems, emphasizing their significance in ensuring precise dengue diagnostics to enhance the efficiency of disease management. These molecular methods are indispensable tools that contribute to accurate diagnosis, enable effective outbreak investigation, facilitate vector surveillance, and support vaccine preparation, thereby enhancing the overall management and control of dengue, ultimately working toward mitigating its impact on public health. Bangladesh J Microbiol, Volume 40, Number 1, June 2023, pp 41-49